THE RHETORIC IMAGINARY OF THE POSTMODERN DISCURSIVENESS - GRADINARU, Camelia (2023)
This paper underlines the relationship between rhetoric and postmodernism. In lack of (and in spite of) a unique definition, postmodernism is seldom described as a non-centred set of rhetorical, critical and discursive practices; rhetoric offers a fertile frame for the interpretation of postmodernism. In my approach, I analyze both the type of rhetoric through which we can grasp the current of postmodernism (the rhetoric of postmodernism) and the use of rhetoric inside the postmodern discursiveness (postmodern rhetoric). The former was born out of its relationship with modernism and from this standpoint I am interested in investigating the rhetorical relevance of themes such as rupture, continuity, palimpsest, anamnesis, incompleteness. The latter is discussed mainly by focusing on the effects of the repositioning of rhetoric in postmodernism. These analyses create a cluster of motifs that constitute the nucleus of the contemporary rhetoric imaginary.